A study on the status of types of vinegar and their rules from Islamic perspective : a case study in the Malaysian market - Iswandi Harahap (International Institute of Halal Research and Training, International Islamic University Malaysia, 2020)
Vinegar is one of the oldest condiments, extracted through the process of fermentation and known to be Prophet Muhammad (S.A.W.)'s one of many favourite foods. For this research, it is focused on investigating various types of vinegar and its hukm (ruling) from the standpoints of fiqh, science, Malaysian Food Act and Regulation and National Fatwa Council. A study upon the status of ruling depending on types of vinegar is utmost crucial, given how there has yet to be a clear guideline in determining ruling across various brands to this very day. Therefore, a further study to clarify its halal status from an Islamic perspective would help in harmonising numerous opinions that have existed among fuqaha. As a whole, the main objective to this study is to analyse and verify the halal status to different types of vinegar available in the Malaysian market. It is determined through the concept of al-tahawwul as to decide fiqh, based on multiple sources on Islamic ruling in classifying the chosen samples into the following three classes: halal, haram and shubhah (doubtful). It is supported with a detailed laboratory research by examining the percentage of both alcohol and acetic acid in vinegar, whereby its result can be used as a guideline in verifying the halal status of respective types. Twenty-five (25) different types of marketed vinegar, produced from different sources and imported from various countries are chosen as the sample. This includes 15 vinegar products in which do not have halal logo on them, while 10 of which that do, 7 products that are extracted through a traditional method and 18 products that are industrially produced (fast-fermentation). By the end of the study, it is found that there are two products classified to be haram, specifically two (2) of them, while the other twenty-three (23) are certified to be halal. In addition to that, it is also found that vinegar product labelled as halal do follow the sharī'ah regulations set by both Malaysian Fatwā Council and JAKIM. Few suggestions and inputs are likewise presented towards the involving parties within this halal industry, let it be the government or respective private organisations to further solidify the halal ruling of products that are generally produced through fermentation such as vinegar or any vinegar-based products. With the validation of halal involving vinegar products, it would be improved the well-being of society and country, simultaneously increase the marketability of every vinegar labelled as halalan tayyiban, not only locally, but likewise internationally.